Determinants of severe acute malnutrition among under-five children in Ethiopia: analysis using data from the 2016 Ethiopia Demographic and Health Survey - Areba, Abriham Shiferaw; Abame, Desta Erkalo; Tirore, Lire Lemma; Bubamo, Bisrat Feleke (Frontiers in Nutrition, 2024)
Objective: Malnutrition is a silent killer that is under-reported, under-addressed, and as a result prioritized. The aim of this study was to determinants of severe acute malnutrition among underfive children in Ethiopia.Methods: Cross-sectional data from the 2016 Ethiopian Demographic and Health Survey were used. A total of 6170 under-five children were included in the current analysis. The data was cleaned and analyzed using STATA 14. An adjusted odds ratio (AOR) and their 95% confidence intervals (CI) were calculated to determine the association between factors and outcomes. A pvalue of less than 0.05 was considered significant in multivariable logistic regression.In multivariable logistic regression revealed that under-five children show that age of children in months 6-11 (AOR=1.52, 95% CI: 1.25, 1.86), 12-23 (AOR=1.98, 95% CI: 1.65, 2.37), and 24-59 months (AOR=1.71, 95% CI: 1.40, 2.08), birth order between 4 th and 5 th (AOR=1.24, 95% CI: 1.01, 1.54), having fever (AOR=1.31, 95% CI: 1.09, 1.58), anemic children (AOR=1.21, 95% CI: 1.07, 1.36), age of mothers in years 25-34 (AOR= 0.60, 95% CI: 0.51, 0.72) and 35-49 (AOR=0.49, 95% CI: 0.39, 0.63), antenatal care visits (AOR=0.83, 95% CI: 0.71, 0.92), rural residence (AOR=2.98, 95% CI: 2.54, 3.49), and solid fuels users (AOR=2.46, 95% CI: 1.86, 3.26) were significant predictors.Conclusions: Older age of children, higher birth order, having fever, anemic children, living rural, and solid fuel users were more suffer from severe acute malnutrition while elder age of mothers and having antenatal care visits reduced severe acute malnutrition from the significant predictors.